Legal Accountability of Deck Officers in Maritime Autonomous Surface Ships: A Normative Analysis of COLREGS and STCW Compliance Gaps in Indonesian Domestic Shipping - Natanael Suranta; Tri Cahyadi; Irfan Faozun (Greenation International Journal of Law and Social Sciences, 2026)
The rapid advancement of Maritime Autonomous Surface Ship (MASS) technology has exposed fundamental normative deficiencies in existing international maritime law, particularly in frameworks governing collision regulations and seafarer certification. This study examines legal accountability in MASS operations, where the traditional human–vessel nexus in COLREGS and STCW is disrupted srupted. Using normative legal and comparative analysis, the study evaluates the adequacy of COLREGS 1972, STCW, SOLAS, and Indonesian Law No. 17 of 2008 in addressing accountability in MASS incidents. Through document analysis of IMO regulatory scoping exercise outputs, EU maritime law developments, and Indonesian domestic shipping regulations, supplemented by thematic expert consultations, the study identifies three principal normative gaps: the absence of a defined legal subject for autonomous decision-making, the inadequacy of STCW competency standards for remote operations, and the fragmented liability regime between flag states, operators, and technology developers. The study proposes a layered normative accountability model tailored to the Indonesian domestic shipping context. Findings contribute to the development of a coherent legal architecture capable of governing the transitional phase of maritime autonomy and offer actionable recommendations for Indonesian maritime regulatory reform.